Treat your back pain without drugs - Jindal, S. R. (New Delhi : Sterling Publishers Pvt. Ltd, 2002)
This sound alternative guide projects alternative methods of cure for back pain without recourse to medicine and drugs - naturopathy, yoga, diet and acupuncture being some of them. Written by a knowledgeable health-care professional, this book will help us understand the basic concept about the spine, how it works, what ails it and how to take proper care.
Keywords: Backache -- Alternative treatment; Backache -- Exercise therapy; Yoga -- Therapeutic use